Illocutionary act in Aquaman Movie Script - Ade Rifky Adrian (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2016)
​This research discusses Illocutionary in the Aquaman movie script based on the theory of George Yule (1996). This research aims to find out how the Illocutionary act is uttered by the main character in the Aquaman movie script. The researcher uses descriptive qualitative as a research method. The sources of data in this research were taken from primary data, namely the movie script Aquaman by internet resources which was taken from seniors that use the movie script as the thesis tolls too and secondary data was taken from audiovisual in the movie Aquaman. The researcher collected data by searching, downloading, reading, watching, pausing, annotating, classifying and coding the data. The data analysis technique is to present, describing, interpreting, and conclude the results of this research. The results show that the Illocutionary act really exists and is applied by the main character in uttering something that refers with the use of the Illocutionary act. Finally, the researcher find 10 data that contained directive, 11 data that contained commissive, 11 data that contained expressive, 3 data that contained declarative, and 2 data that contained representative Illocutionary act. Commisive and expressive is the aspect that is more dominantly uttered by the main character in the object, in the Aquaman movie script contained the usage of the illocutionary act which Illocutionary act is the act of doing something and affecting the listener.